Autopsy versus clinical decisions regarding causes of maternal Death in Iraq - Batool Ali Ghalib Yassin; Aliaa Makki Hassan AL-Safi; Enaam Hasson AL-Saneed (Wolters Kluwer Medknow Publications, 2022)
Background: Complications during pregnancy and childbirth are a leading cause of death and disability among women in developing countries. The target for mortality reduction is important, yet accurate data of maternal mortality remains challenging as reporting errors including misclassification of cause of death continue to pose a major challenge. Objectives: This study aimed to identify if there is any discrepancy between clinical and autopsy causes of maternal death. Methods: A review of all maternal deaths records that had two sources for registered cause of death; one made by the obstetrician depending on clinical setting and the other by forensic medicine after autopsy and search for any discrepancies between the two sources. Results: A total of 468 maternal death reports were reviewed; the discrepancies were more with the second commonest cause of maternal death in Iraq which is pulmonary embolism. The review revealed that 10.1% of those clinically died because of pulmonary embolism turned to be dead from other causes; 8.7% of them from postpartum hemorrhage, and the rest from sepsis and other indirect causes. Conclusion: There is a substantial discrepancy between clinical and autopsy causes of maternal death which necessitates asking for autopsy in cases of maternal mortality of uncertain cause. The use of maternal death review within 3-6 weeks of death as a tool to identify causes of maternal deaths is recommended.